Another time, another place eaudiobook - Taylor, Jodi (Chronicles of St. Mary's, 2021)
The twelfth book in the bestselling Chronicles of St Mary's series. If you love Jasper Fforde, Ben Aaronovitch or Doctor Who, you won't be able to resist Jodi Taylor. 'It's time, Max.' And so, a whole new chapter opens up... It's long been known that if a thing can go wrong, it will. With knobs on, usually. Disasters start to pile up. A new colleague with no respect for the past and a great deal to prove. Historians lost in time. And—worst of all—Rosie Lee on her very first jump. Then there's the small matter of Max's dishonourable discharge. From Tudor England to the Tower of Babel—it's all going horribly wrong. Jobless and homeless, Max receives an offer she can't refuse. Another time, another place. A refuge, perhaps. She's got that wrong, too. (P)2021 Headline Publishing Group Limited